Respiratory System Science Flashcards: Media Innovation for Grade VIII Students - Mellisa Mellisa; Riadatil Fitri; Delma Saputri (Journal of Natural Science and Integration, 2026)
The observations and interviews with teachers and students indicate that it is still difficult to understand and memorize, especially on specific topics, such as the human respiratory system. The learning process still tends to rely on lectures and PowerPoint presentations. It uses teacher textbooks as media in the science learning process, making it less active and less enjoyable. This study aims to develop a valid and practical flashcard learning medium for grade VIII SMP/MTS students on the human respiratory system sub-material. This research is included in the development research (R&D) using the Plomp development model. The data collection instruments used are student and teacher interview sheets, student needs questionnaires, self-evaluation sheets, validation sheets, one-to-one evaluation test questionnaires, small-group tests, and validated practicality questionnaires or field tests. The sampling technique used is simple random sampling. The results of the material expert validation averaged 88% in the valid category. The results of the media expert validation averaged 97%, with a very valid category. The results of the learning expert validation averaged 97%, with a very valid category. The practicality test averaged 90%, categorizing it as very practical. The conclusion is that the flashcard learning media for the human respiratory system sub-topic is highly valid and very practical. Keywords: human respiratory system, development, flashcard